Frequency of Impaired Glucose Tolerance in Women with Polycystic Ovary Syndrome (PCOS) - Bazla Younas, Nisha Tabassum, Shafia (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of impaired glucose tolerance in women with polycystic ovary syndrome (PCOS). Study Design: Cross-sectional study Place and Duration: Department of Obstetrics and Gynaecology, Unit-I, ShaheedMohtarma Benazir Bhutto Medical University of Medical Sciences, Larkana. Study was carried out over a period of six months from 23rd March 2018 to 22nd September 2018. Subjects and Methods: A total of 120 patients were recruited in this study. 75g oral glucose tolerance test was performed. The 2ml blood sample was obtained by using BD syringe. Those patients having whole blood glucose value >140-200mg/dl were labeled as having impaired glucose tolerance test. Results: Mean age of the patients was 24.6±6.4 years. Mean BMI 28.5±2.8 kg/m2. Out of 120 cases, 69 patients (57.5%) were married while remaining 51 patients (42.5%) were unmarried. Out of 69 married patients, 24 (34.8%) were primigravida and 45 (65.2%) were multigravida. Mean duration of PCOS was 1.6±0.8 year. Frequency of IGT was observed in 20 patients (16.7%). Symptoms were as follows: Oligomenorrhea 58 (48.3%), hyper-androgenium 29 (24.2%) and increased ovarian volume 33 (27.5%). Stratification with regard to age, BMI, marital status, parity, duration of PCOS and symptoms was also carried out. Conclusion: Women with PCOS are at a high risk for the development of IGT (16.7%) and subsequently Type 2 DM. While managing the hirsutism and menstrual irregularities, metabolic evaluation of the patient should be done. Keywords: Polycystic ovarian syndrome, Impaired glucose tolerance, Androgen excess